Switching pulse generation for DC-DC boost converter using Xilinx-ISE with FPGA processor - R. Palanisamy; K. Vijayakumar (Institute of Advanced Engineering and Science, 2019)
This paper explains steps to generate switching pulse using Xilinx-ISE with FPGA processor for DC-DC boost converter. The switching pulse generated using Very high speed integrated circuit Hardware Description Language (VHDL) with Xilinx-ISE. VHDL is a programming language, which is used to model and design any complex circuits in a dynamic environment. This paper gives the course of action for generation of switching pulses for dc-dc boost converter using Xilinx-ISE and matlab simulink. The switching pulse generated using Xilinx-ISE with FPGA-Spartan 6 processor compared with switching pulse generated using matlab.